2011
DOI: 10.1021/jp1120756
|View full text |Cite
|
Sign up to set email alerts
|

Phase and Microphase Separation of Polymer Thin Films Dewetted from Silicon—A Spin–Echo Resolved Grazing Incidence Neutron Scattering Study

Abstract: An understanding of the structure of ultrathin polymer films on solid substrates has scientific importance in applications as well as in fundamental studies of polymer diffusion or adsorption. We present studies of the organization of dewetted droplets of polymers on a silicon surface using a new neutron scattering technique, spin-echo resolved grazing incidence scattering (SERGIS), that has the potential to address at the same time the droplet-droplet correlations and the chemical configuration inside each dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Repeat steps 3.6.1-3.6.3 for any further samples that need to be measured. 7. The collected data consists of both spin up and spin down 2D intensity maps for each sample.…”
Section: Sergis Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat steps 3.6.1-3.6.3 for any further samples that need to be measured. 7. The collected data consists of both spin up and spin down 2D intensity maps for each sample.…”
Section: Sergis Experimentsmentioning
confidence: 99%
“…Inelastic spin echo techniques were developed by Mezei et al 1 in the 1970s. Since then the SERGIS technique (which is an extension of the ideas of Mezei et al) has been successfully demonstrated experimentally using a variety of samples such as highly regular diffraction gratings [2][3][4][5][6] and circular de-wetted polymer droplets 7 . A dynamical theory has been developed by Pynn and coworkers to model the strong scattering from highly regular samples [3][4][5][6]8 .…”
Section: Introductionmentioning
confidence: 99%
“…Other applications of NR include investigating block copolymer morphologies, (108 -110) the mobility of polymer segments in confined geometries, (111,112) and examining the interface and adhesion of polymers on substrates. (113,114) Instruments to carry out in situ NR on samples undergoing shear flow have been developed. (115) (104) with permission).…”
Section: Neutron Reflectionmentioning
confidence: 99%
“…As a result, large sample areas are required and the instrument performs more like a reflectometer. An attempt to make effective use of divergent neutron beams is the use of spin polarised neutrons together with magnetic fields for Lamor precession to encode the scattering angle with so-called spin-echo-resolved grazing incidence scattering (SERGIS) 11 13 . Instead of spatial angular resolution this method measures the depolarization of the beam to record very week scattering of neutrons in the sample plane.…”
Section: Introductionmentioning
confidence: 99%